University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 11 - Section 11.1 - Three-Dimensional Coordinate Systems - Exercises - Page 600: 53


$(x + 1)^2+(y -\dfrac{1}{2})^2+(z+ \dfrac{2}{3})^2=\dfrac{16}{81}$

Work Step by Step

We know that the standard equation of a sphere is written as: $(x-x_0)^2+(y-y_0)^2+(z-z_0)^2=r^2\ \ \ $ (1) Here, $(x_0,y_0,z_0)$ represents the center and $r$ is the radius of the sphere. Since, we have $x_0=-1,y_0=\dfrac{1}{2},z_0=\dfrac{-2}{3}, r=\dfrac{4}{9}$ Plug all the above values in equation (1), then we get Thus,, $(x - (-1))^2+(y -(\dfrac{1}{2}))^2+(z - (\dfrac{-2}{3}))^2=(\dfrac{4}{9})^2$ Hence, $(x + 1)^2+(y -\dfrac{1}{2})^2+(z+ \dfrac{2}{3})^2=\dfrac{16}{81}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.